Podiform Chromitites in the Sorkhband Ultramafic Complex, Southern Iran: Evidence for (Journal of Sciences, Islamic Republic of Iran)
The podiform chromitite deposits of the Ordovician Sorkhband ultramafic complex, southwestern Makran, are the largest chromitite deposits in Iran. The Sorkhband ultramafic complex comprises of a northern part of dunite, podiform chromitite, olivine clinopyroxenite, wehrlite and olivine websterite and a southern part of foliated diopsidic harzburgite with subordinate dunite, olivine clinopyroxenite dykes and no significant chromitite mineralization. The podiform chromitites in the northern part occur almost exclusively in dunite, which is depleted in highly siderophile elements (HSE), and display massive, disseminate, banded and nodular textures. These chromitites consist of compositionally uniform chromite with molar 100Cr/(Cr+Al) values (i.e., Cr#) ranging from 75 to 89. Diopsidic harzburgite contains accessory chromite with a wide variation in Cr# from 13 to 40, and shows evidence of melt-rock interaction. Dunite in the northern part contains euhedral accessory chromite (Cr# = 65-80) intermediate between those in diopsidic harzburgite and chromitites. Chromite in the chromitites has strongly fractionated chondrite-normalized PGE patterns, which are characterized by enrichments in Os, Ir, Ru and Rh relative to Pt and Pd. The chromite compositions and PGE geochemistry suggest that the chromitite deposits of the Sorkhband ultramafic complex formed from a boninitic melt under low oxygen fugacity in a supra-subduction setting environment.